An Investigation of the Effect of Parameters and Chip Slenderness Ratio on Drilling Process Quality of AISI 1050 Steel - Zülküf Demir; Rifat Yakut (Advances in Materials Science and Engineering)
The chip slenderness ratio is a vital parameter in theoretical and applicable machining operations. In predrilled drilling operations of AISI 1050 steel alloy, HSS drills were employed, and the effect of the selected parameters on the chip slenderness ratio and also the effect of the chip slenderness ratio on the thrust force, surface roughness, drilled hole delamination, tool wear, and chip morphology were investigated. The major parameters, influential on the chip slenderness ratio, were feed rate and point angle, while spindle speed was too small to be negligible. With increasing the chip slenderness ratio, the thrust force and the tool wear decreased, which resulted in appropriate chip morphology, but there were increases in surface roughness. However, the chip slenderness ratio had no effect on the drilled hole delamination.